PHYSICAL ACTIVITY AND DIETARY HABITS OF FILIPINO COLLEGE STUDENTS: A CROSS-SECTIONAL STUDY (Kinesiology, 2018)
No published study has been tracked to date on the physical activity (PA) and dietary habits (DH) of Filipino college students. Thus, this cross-sectional study aimed to determine (1) the prevalence of regular PA among college students in a Philippine setting and (2) the reasons for either adherence to PA or for being inactive, (3) to describe DH of the students, (4) to compare PA involvement and DH across year levels, and (5) to correlate PA and diet behaviors. Data were collected using a self-administered survey questionnaire. Results showed that only 32.8% of the 1,706 students in this study engaged in regular PA. There were greater proportions of inactivity at higher-year levels (62.5%, 66.5%, 76.5%, and 84.8% in the first, second, third and fourth year, respectively). The major reason for inactivity was lack of time, while the students’ PA adherence was largely due to predisposing factors such as knowledge about PA, beliefs in benefits and enjoyment of PA, and confidence in performing physical activity. About one of every three students in each year level had below-average to poor dietary habits, meaning they seldom eat proper types of food. Findings of this study indicate the need for an intervention that will effectively increase regular PA and ensure proper food intake in the student population.Key words: exercise, food intake, university students